The Effect of Service Quality and Product Quality (Rooms and Food) on Consumer Satisfaction of Harris Sentul Hotel Bogor - Hamdany, Hamdany; Mumin, Adhi Trirachmadi; Lemmy, Diena Mutiara (Institut Pariwisata Trisakti, 2019)
Research on the influence of two independent variables namely service quality and product quality (of room and food) conducted at Harris Hotel Sentul Bogor aims to examine the level of its influence either partially or simultaneously on customer’s satisfaction as the dependent variable. The dimensions of service quality that are examined in terms of its influence on consumer satisfaction include elements of reliability, assurance, tangible, empathy and responsiveness. Some of the product quality indicators for the rooms quality examined to have its influence on customer satisfaction include elements of design, features, quality of performance and the perceive of quality while indicators for the quality of food products which considered to have effect on consumer satisfaction includes the element of taste of food, aroma of food and the presentation of food. The number of respondents who took part in the research was 300 of respondents who were the consumers invited to share their experience on the questioner during their stay at Harris Sentul Hotel. Data analysis techniques used in this study are linear regression analysis. The study results have answered the 3 hypotheses and show that service quality has a positive and significant influence on customer satisfaction partially likewise, the study results has showed that the quality of room and food have a strong influence on the level of customer satisfaction who stayed at Harris Sentul as well as study has showed that simultaneously the 2 (two) independent variables had a positive and significant effect.